Emission and control of trace elements from coal-derived gas streams - Zhao, Yongchun; Li, Hailong; Yang, Jianping; Zhang, Junying; Zheng, Chuguang (Woodhead Publishing in energy., 2019)
Emission and Control of Trace Elements from Coal-Derived Gas Streams presents an up-to-date and focused analysis on Trace element (TEs) emissions and control strategies during coal utilization. This book provides insights into how TE's in coal are distributed from different coal-forming periods, coal ranks and coal-bearing regions. As the emission and control of TEs during coal utilization are a significant concern, this book introduces TEs in coal and pollution in an accessible way before discussing why they occur and how they are distributed during various stages of coal forming, also considering various regions and countries. Specific types of TEs in relation to partition in coal combustion, coal fires, gasification and coal feed furnace are then analyzed, providing the reader with practical knowledge to apply to their own research or projects. This book is an essential reference for energy engineers researching and working in coal technology, with a specific focus on emission control, as well as graduate students and researchers in energy engineering, environmental, thermal and chemical engineering who have an interest in trace element emission and control from coal utilization. Presents characteristics of TE emissions during coal utilization in laboratory-scale experiments, industrial furnaces and power plantsConsiders different legislation and case studies from various regions and countriesIncludes contributions from world renowned expertsPresents a concise and focused analysis on TE emissions and control strategies